BIOLOGICAL CONTROL OF BASAL STEM ROT DISEASE OF COCONUT - R. Bhaskaran; N. Ramadoss; A. Karthikeyan; T.K. Ramachandran (International Coconut Community Journal, 1993)
Trichoderma harzianum multiplied in farm yard manure and applied with neem cake to coconut palm affected by basal stem rot disease reduced the severity of the disease. T harzianum applied in coconut basins survived for more than one year, though the population gradually declined after four months. Application of Azotobacter or phosphobacterium (200 g peat based inoculurn) to basal stern rot disease affected coconut gave lesser increase in disease index than control and increased the nut yield. Tapping for neera production in mild and moderately diseased palms showed lesser disease index than untapped palms of corresponding disease severity.